Determining the impact of Heligmosomoides polygyrus infection on the development of colitis - Katsandegwaza, Brunette (Department of Pathology, 2020)
The ability of helminths to regulate inflammatory disorders and the mechanisms by which they carry this out are of great scientific interest. Currently, established literature emphasises the protective role of helminth infection in mouse models of inflammatory bowel disease (IBD). Utilising two well-established murine models of human disease, the oxazolone and dextran sulfate sodium (DSS) models, I found that induction of murine IBD is highly sensitive to diet change and mouse gender. Using the gastrointestinal helminth Heligmosomoides polygyrus (H.polygyrus), I demonstrate that helminth infection exacerbates IBD in both the oxazolone and DSS models of colitis. Underlying helminth infection results in increased inflammation locally in the colon and systemically in the spleen in both models of IBD, as measured by histology and flow cytometry. Exacerbation of DSS colitis is dependent on the dose of H.polygyrus but is independent of the phase of H.polygyrus infection, with both acute and chronic infections resulting in the same phenotype. Helminth exacerbated DSS colitis is characterised by significant bacterial translocation to the spleen, which is concluded to be due to loss of intestinal epithelial integrity. Helminth infection also resulted in a microbial shift of translocating bacteria following DSS administration, as evidenced by gram staining and bacterial sequencing. Administration of an 8- strain probiotic during acute helminth infection ameliorated helminth exacerbation of DSS colitis, restored epithelial integrity and abrogated splenomegaly. This work uncovers an unexpected and novel role for live helminth infection in exacerbating IBD and suggests that helminth-induced dysbiosis of the microbiota may drive disease. These studies reveal restoration of the microbiota through probiotics or helminth eradication as potential therapies for the treatment of gastrointestinal inflammatory disorders.